2017
DOI: 10.1371/journal.pone.0173821
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference genes for qRT-PCR analysis during biological invasions: The thermal adaptability of Bemisia tabaci MED

Abstract: The Bemisia tabaci Mediterranean (MED) cryptic species has been rapidly invading to most parts of the world owing to its strong ecological adaptability, which is considered as a model insect for stress tolerance studies under rapidly changing environments. Selection of a suitable reference gene for quantitative stress-responsive gene expression analysis based on qRT-PCR is critical for elaborating the molecular mechanisms of thermotolerance. To obtain accurate and reliable normalization data in MED, eight cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 77 publications
3
25
1
Order By: Relevance
“…Although β-ACT and ArgK are traditional reference genes and have been used in many gene expression studies, they are not always stably expressed. Consistent with our results, many studies have shown unstable expression of β-ACT under variable conditions in a variety of species, including Bemisia tabaci 40 , M. separata 35 , F. occidentalis 39 , Henosepilachna vigintioctopunctata 41 , P. japonica 38 , Hippodamia convergens 42 and C. maculata 30 , as well as for ArgK in Spodoptera litura 43 , P. japonica 38 , C. maculata 30 and E. onukii 8 .…”
Section: Experimental Conditionsupporting
confidence: 92%
“…Although β-ACT and ArgK are traditional reference genes and have been used in many gene expression studies, they are not always stably expressed. Consistent with our results, many studies have shown unstable expression of β-ACT under variable conditions in a variety of species, including Bemisia tabaci 40 , M. separata 35 , F. occidentalis 39 , Henosepilachna vigintioctopunctata 41 , P. japonica 38 , Hippodamia convergens 42 and C. maculata 30 , as well as for ArgK in Spodoptera litura 43 , P. japonica 38 , C. maculata 30 and E. onukii 8 .…”
Section: Experimental Conditionsupporting
confidence: 92%
“…Production of dsRNA transcription templates and dsRNA synthesis dsRNA targeting MED Dnmt3 and eGFP was synthesised via PCR and in vitro transcription as described by Dai et al (2017). PCR using specific primers with a T7 RNA polymerase promoter generated a product that was subsequently employed as a template for in vitro transcription using a MEGAscriptT7 High Yield Transcription Kit (Ambion, Austin, TX, USA).…”
Section: Bioinformatics Characterization Of the Btdnmt3 Genementioning
confidence: 99%
“…All amplifications were confirmed via sequencing, and the specificity of qRT-PCR was estimated through melting curve analysis. Beta-1-tubulin (b-tub) and elongation factor 1 alpha (EF1-a) were used as internal controls to normalize the relative expression of Dnmt mRNA (Dai et al, 2017). A reaction volume of 20 ll was employed, containing 1.0 ml cDNA template, 10.0 ml of 23 TransStart TM Green qPCR SuperMix (Transgen), 0.3 ml of each primer (10 lM), 0.4 ml passive reference dye and 8.0 ll doubledistilled H 2 O.…”
Section: Qrt-pcrmentioning
confidence: 99%
“…; Dai et al . ). Therefore, it is necessary to evaluate the stability of reference genes under specific experimental conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Housekeeping genes have been conventionally used for reference genes in RT-qPCR analysis, including 18S rRNA, Actin, Tubulin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), elongation factor-1 (EF-1), ribosomal protein (RP) and TATA binding protein (TBP) (Ponton et al 2011;Zhong et al 2013;Avicor et al 2014;Cardoso et al 2014;Zhai et al 2014). Nevertheless, some studies have reported that the expression of universal reference genes can show great variation across different tissues and developmental stages and under different experimental treatments Collins et al 2014;Dai et al 2017). Therefore, it is necessary to evaluate the stability of reference genes under specific experimental conditions.…”
Section: Introductionmentioning
confidence: 99%